Modeling of guide sign illumination and retroreflectivity to improve driver’s visibility and safety - Obeidat, Mohammed (Kansas State University, 2015)
This dissertation is the result of studying different methods of increasing guide sign visibility and legibility to drivers during nighttime, to increase safety on roadways. It also studies intersection lighting to indicate the lighting benefits on nighttime crash frequency reduction. From a survey conducted, practices related to overhead guide sign illumination and retroreflectivity in United States were summarized. A laboratory experiment was conducted to compare light distribution of five light sources: Metal Halide, Mercury Vapor, High Pressure Sodium, induction lighting, and Light Emitting Diode (LED). Cost analysis of the five light sources was performed. Combining results of the laboratory experiment and the cost analysis, induction lighting was recommended for states that want to continue external sign illumination. A retroreflectivity experiment was conducted to compare three types of retroreflective sheeting: Engineering Grade (type I), Diamond Grade (type XI), and High Intensity (type IV), to determine the sheeting that best increases visibility and legibility. Diamond Grade (type XI) was found to be the optimal sheeting that increases visibility and legibility to drivers during nighttime. A glare experiment was conducted to expand the retroreflectivity experiment results. Four sheeting-font combinations of High Intensity (type IV) and Diamond Grade (type XI) materials and Series E (Modified) and Clearview fonts were compared. Results revealed an optimal sheeting-font combination of Diamond Grade (type XI) sheeting and Clearview font which increases the visibility and legibility of guide signs to drivers under presence of oncoming glare source. The Highway Safety Information System (HSIS) database was used to study the effect of intersection lighting on the expected crash frequency. Illuminated intersections showed 3.61% and 6.54% decrease in the expected nighttime crash frequency as compared to dark intersections in Minnesota and California, respectively. In addition, partial lighting at intersections decreases the expected nighttime crash frequency by 4.72% compared to continuous lighting in Minnesota. The recommended sheeting-font combination for Departments of Transportation was Diamond Grade (type XI) and Clearview. This combination will increase signs’ visibility and legibility to drivers, and consequently increase safety on roadways. Adding partial lighting at intersections will reduce the expected nighttime crash frequency, and increase safety on roadways.
Keywords: Light sources and retroreflective sheeting material; Older age drivers; Guide sign visibility when glare present; Guide sign visibility and legibility improvement during nighttime; Increasing driver's safety on roadways during nighttime; Intersection lighting; Engineering (0537); Industrial Engineering (0546)